PENGARUH TRAINING EMPLOYEE DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN - Indriani, Rika; Mulia, Faizal; Jhoansyah, Dicky (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
The purpose of this study is to measure the effect of employee training and work ability on employee performance. The method used in this research is descriptive and associative methods with quantitative approaches. The sampling technique in this study uses non-probability sampling using a purposive sample or sample consideration / aims, and in this case only employees of the marketing department numbering 155 employees at PT. World Innovative Telecommunication Sukabumi Branch. The data analysis technique used is multiple linear regression analysis techniques. The results of the study, using the F test the probability value sig. 0.00 <0.05 which means that together employee training (X 1 ) and work ability (X 2 ) have a significant influence on employee performance (Y). While the t test shows that employee training (X 1 ) has a significant influence on employee performance (Y) and work ability (X 2 ) has a significant effect on employee performance (Y).